2008
DOI: 10.1086/529488
|View full text |Cite
|
Sign up to set email alerts
|

The Most Dark‐Matter–dominated Galaxies: Predicted Gamma‐Ray Signals from the Faintest Milky Way Dwarfs

Abstract: We use kinematic data from three new nearby, extremely low luminosity Milky Way dwarf galaxies (Ursa Major II, Willman 1, and Coma Berenices) to constrain the properties of their dark matter halos, and from these we make predictions for the -ray flux from annihilation of dark matter particles in these halos. We show that these $10 3 L dwarfs are the most dark-matter-dominated galaxies known, with total masses within 100 pc that are in excess of 10 6 M . Coupled with their relative proximity, their large masses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
274
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(293 citation statements)
references
References 70 publications
18
274
0
Order By: Relevance
“…Observations in the hard X-ray band would also be useful; however, as opposed to clusters of galaxies, where the effect of diffusion on the dark matter multiwavelength SED is typically mild (see Colafrancesco et al 2006;Profumo 2008a), in dSph galaxies high-energy electrons and positrons escape more efficiently from the diffusive region, suppressing the hard X-ray emission. Strigari et al (2008) recently estimated the gamma-ray flux from dark matter annihilation in newly discovered, extremely low luminosity and dark matter dominated Milky Way dwarf galaxies. The expected gamma-ray flux from these nearby galaxies may be larger than that from previously known dwarfs, depending on the so far poorly known dark matter density distribution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Observations in the hard X-ray band would also be useful; however, as opposed to clusters of galaxies, where the effect of diffusion on the dark matter multiwavelength SED is typically mild (see Colafrancesco et al 2006;Profumo 2008a), in dSph galaxies high-energy electrons and positrons escape more efficiently from the diffusive region, suppressing the hard X-ray emission. Strigari et al (2008) recently estimated the gamma-ray flux from dark matter annihilation in newly discovered, extremely low luminosity and dark matter dominated Milky Way dwarf galaxies. The expected gamma-ray flux from these nearby galaxies may be larger than that from previously known dwarfs, depending on the so far poorly known dark matter density distribution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Under the assumption of a particular DM density distribution profile, the flux upper limits can be used to set upper bounds on σ A v . Dwarf spheroidal galaxies have the advantage that the integrated J-factor is relatively insensitive to the choice of a DM density profile [31,32]. The bounds on the annihilation cross sections of χ are obtained from the recent results of Fermi-LAT [26] where the negative search of gamma rays coming from 15 dwarf spheroidal satellite galaxies of the Milky Way is used to set upper limits on the DM annihilation cross section into certain channels, namely e + e − , µ + µ − , τ + τ − , uu, bb and W W .…”
Section: Experimental Inputmentioning
confidence: 99%
“…However, it has been argued that effects in the halo distribution alone can only be expected to account for a boost factor of ∼ 2 − 3, due to the uncertainty in the estimation of the local halo abundance [44]. A possible additional factor < ∼ 10 could arise from substructure within the Milky-Way halo [45], and, for signals from dwarf galaxies, there could possibly be a factor < ∼ 100 [46]. In this work we will focus on models that best fit the data with B < 200.…”
Section: Jhep01(2011)064mentioning
confidence: 99%
“…12 Although, as emphasized in [46,103], stellar kinematic data fix the normalization of ρ and ρ 2 such that the detailed nature of the inner-slope of the halo ends up having a relatively small effect on the total halo integral. 13 A rough calculation of these contributions (without any attempt to include the LAT instrument response) showed that the line contribution to the total yield of gammas would be > 1% in only ≈ 0.5% of the models in our pMSSM set.…”
Section: Jhep01(2011)064mentioning
confidence: 99%